Obowiązek naprawienia szkody jako środek karny a roszczenia cywilnoprawne - Citowicz, Rafał; Pieszczek, Martyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This article contains the analysis of the obligation to compensate the damage, being one of the possible penalties. The authors note that the criminal law and criminal proceedings reform from 1997 significantly changed the status of the victim in criminal and preparatory proceedings. It involved a new philosophy of criminalisation, which may be expressed in saying that one of the most important aims of the criminal proceedings is to solve the conflict between the offender and the victim, resulting from the offence committed against the latter. This conflict may be solved or considerably alleviated if the damage caused to the victim is compensated for and therefore Article 39 item 5 of the Polish Criminal Code provides for the obligation to compensate for the damage. The paper focuses on conditions for the judgement ordering compensation for damage caused as a result of an offence. The crucial point of the article is a description of distinctions between the civil and criminal cases connected with claims for damages against an offender.
Keywords: obowiązek naprawienia szkody; krzywda moralna; roszczenia cywilne